2017
DOI: 10.3168/jds.2016-12046
|View full text |Cite
|
Sign up to set email alerts
|

Management practices, physically effective fiber, and ether extract are related to bulk tank milk de novo fatty acid concentration on Holstein dairy farms

Abstract: The objective of this study was to evaluate the relationship of management practices and dietary factors with de novo fatty acid concentration in bulk tank milk from commercial dairy farms milking Holstein cows. Farms were selected based on de novo fatty acid concentration during the 6 mo before the farm visit and were categorized as high de novo (HDN; 24.61 ± 0.75 g/100 g of fatty acids, mean ± standard deviation; n = 19) or low de novo (LDN; 23.10 ± 0.88 g/100 g of fatty acids; n = 20). Farms were visited on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
(54 reference statements)
5
28
2
1
Order By: Relevance
“…Descriptive statistics for milk FA profile of bulk tank samples are presented in Table 1. In the current study, we observed generally positive relationships of de novo-synthesized short-chain FA with herd milk fat percentage (P = 0.002; R 2 = 0.12), consistent with the previous observations (Barbano et al, 2014;Woolpert et al, 2016Woolpert et al, , 2017. We also noted a generally negative relationship of trans C18:1 isomers that are produced by other alternate pathways of ruminal biohydrogenation with herd milk fat percentage.…”
supporting
confidence: 91%
“…Descriptive statistics for milk FA profile of bulk tank samples are presented in Table 1. In the current study, we observed generally positive relationships of de novo-synthesized short-chain FA with herd milk fat percentage (P = 0.002; R 2 = 0.12), consistent with the previous observations (Barbano et al, 2014;Woolpert et al, 2016Woolpert et al, , 2017. We also noted a generally negative relationship of trans C18:1 isomers that are produced by other alternate pathways of ruminal biohydrogenation with herd milk fat percentage.…”
supporting
confidence: 91%
“…Days post parturition had a significant effect on the de novo fatty acid index (C4:0 to C15:0) (p = 0.028). De novo fatty acids, which are the fatty acids synthesised in the cows mammary gland from the volatile fatty acids acetate and butyrate, have increasingly been used as an indicator of rumen function on commercial dairy farms (Woolpert et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…To compensate pasture quality variability and scarcity, sheep farms usually integrate animal diets with grain and mixes concentrates from both local and international markets. It has to be noticed that milk FA composition is also related to the herbage quality and to the intake of glucogenic and lipogenic carbohydrates; elevated intake of FA precursors from high digestible forages is associated with increases in de novo FA (Woolpert et al 2017). Thus, an increase in de novo FA is expected in winter and early-spring with high herbage availability and intake, whereas a decrease is expected late-spring and summer because the lower pasture fibre quality.…”
Section: Milk Qualitymentioning
confidence: 99%